Frontline Science: Exhaustion and senescence marker profiles on human T cells in BRGSF-A2 humanized mice resemble those in human samples. Issue 1 (4th August 2019) - Labarthe, Laura; Henriquez, Soledad; Lambotte, Olivier; Di Santo, James P.; Le Grand, Roger; Pflumio, Françoise; Arcangeli, Marie-Laure; Legrand, Nicolas; Bourgeois, Christine
Abstract: This work sought to confirm the human-like expression of exhaustion and senescence markers in a mouse model with a humanized immune system (HIS): the Balb/c Rag2 KO IL2rgc KO Sirpα NOD Flk2 KO HLA-A2 HHD (BRGSF-A2) mouse reconstituted with human CD34 + cord blood cells. With regard to senescence markers, the percentage of CD57 + T cells was higher in the bone marrow (BM) than in the spleen or blood. The same was true for KLRG1 + hCD8 + T cells. With regard to exhaustion markers, the percentage of programmed death 1 (PD-1 + ) T cells was higher in the BM than in the spleen or blood; the same was true for TIGIT + hCD4 + cells. These tissue-specific differences were related to both higher proportions of memory T cells in BM and intrinsic differences in expression within the memory fraction. In blood samples from HIS mice and healthy human donors (HDs), we found that the percentage of KLRG1 + cells among hCD8 + T cells was lower in HIS compared to HDs. The opposite was true for CD4 + T cells. Unexpectedly, a high frequency of KLRG1 + cells was observed among naive T cells in HIS mice. CD57 expression on T cells was similar in blood samples from HIS mice and HDs. Likewise, PD-1 expression was similar in the two systems, although a relatively low proportion of HIS hCD4 + T cells expressed TIGIT. The BRGSF-A2 HIS mouse's exhaustion and senescence profile was tissue specific and relatively human like; hence, this mouse might be a valuable tool for determining the preclinical efficacy of immunotherapies.